Population dynamics of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) in Samendéni reservoir, Burkina Faso - Raogo Blaise Ouédraogo; Souleymane Sanogo; Inoussa Compaoré (Fisheries and Aquatic Sciences)
The estimation of growth and exploitation parameters is essential for understanding the population dynamics, life history, and ecological interactions of fish species. This study investigated the growth, mortality, and exploitation rates of the Oreochromis niloticus population in Samendéni reservoir, located in the West Sudanian savannah in the Region of Hauts-Bassins, Burkina Faso. Fish samples were collected monthly, from October 2021 to September 2022. The total length (TL) and weight of each sample were measured. Thus, the length-frequency data of 1,268 specimens were measured from 9 to 32 cm in TL. Furthermore, different modal distributions, such as unimodal, bimodal, and trimodal, were observed due to various monthly data sizes. Monthly data were grouped into length classes of 1 cm intervals, and all datasets were analyzed using the electronic length frequency analysis (ELEFAN) method incorporated in the FISAT software (FISAT II; FAO, Roma, Italia). The analysis revealed a growth constant of 0.44 year-1 and an asymptotic length (L∞) of 33.6 cm in TL for the population. The growth performance index was estimated at 2.696, while longevity and age at length zero (t0) were estimated at 6.818 years and –0.643 years, respectively. Furthermore, by comparing the lengths at first capture (Lc = 10.77 cm) and first maturity (Lm50 = 19 cm for males and 21.78 cm for females), it was evident that most harvested stocks were juveniles. Moreover, the coefficients for total mortality, natural mortality, and fishing mortality were 3.19, 1.04, and 2.15 year⁻¹, respectively. The recruitment pattern followed a continuous model, with a single peak, indicating a recruitment period in July. Based on the current exploitation rate E (E = 0.67), which was respectively higher than the optimal exploitation rate (Eopt = 0.5) and the yield per recruit (Emax = 0.570), the species was found to be in an overfishing situation. However, as the catch consisted of more juvenile individuals, increasing fishing gear mesh size, regulating fishing efforts, and providing vocational training to fishermen with the support of community leaders, fisheries scientists, and government representatives are needed to protect the O. niloticus stock in Samendéni reservoir.